Halal Economy in Nigeria: Examining the Legal Framework and Certification Dynamics for Sustainable Growth - Muhammad, Adamu Abubakar; Lateef, Abiola Muideen; Ardo, Adam Muhammad; Shahbaz, Athar; Khatoon, Ghousia (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2026)
This paper seeks to examine the opportunities and challenges posed by the ?al?l business in Nigeria and its certification according to laws. It provides a comprehensive review of the sector, outlining its structure, current state, potential for growth and the intimidating challenges in the operational and legal circle. ?al?l industry is an emerging sector with great potential for growth and economic development in Nigeria. The large Muslim population is a driving factor that creates opportunities for its growth to improve the national economy. However, these opportunities, as well as the impeding challenges, have still been poorly understood. The paper draws data from both primary and secondary sources; obtained from interviews, industry literature, government laws and reports. The paper found that legal provision of halal industry in Nigeria can create more opportunities in the country’s trade and commerce sector by expanding the production of locally grown food, creating economic linkages, developing an export market, booming tourism and hospitality sectors; and thus become a major source of employment in the country. However, a number of challenges such as inadequate infrastructure, insufficient access to finance, and a lack of regulatory framework could hamper the growth of the industry; and therefore, need to be addressed. The paper conclude that with the proper policy interventions and investment, the ?al?l industry in Nigeria has the potential to create significant economic, social, and environmental benefits [Tulisan ini bertujuan untuk mengkaji peluang dan tantangan yang ditimbulkan oleh bisnis ?al?l di Nigeria serta sistem sertifikasinya berdasarkan ketentuan hukum yang berlaku. Kajian ini menyajikan tinjauan komprehensif mengenai sektor tersebut dengan menguraikan struktur, kondisi terkini, potensi pertumbuhan, serta berbagai tantangan signifikan dalam aspek operasional dan hukum. Industri ?al?l merupakan sektor yang sedang berkembang dengan potensi besar untuk mendorong pertumbuhan dan pembangunan ekonomi di Nigeria. Jumlah penduduk Muslim yang besar menjadi faktor pendorong utama yang membuka peluang bagi pengembangan sektor ini guna meningkatkan perekonomian nasional. Meskipun demikian, berbagai peluang tersebut beserta tantangan yang menghambatnya masih belum dipahami secara memadai. Penelitian ini menggunakan data yang bersumber dari data primer dan sekunder, yang diperoleh melalui wawancara, literatur industri, peraturan perundang-undangan, serta laporan pemerintah. Hasil penelitian menunjukkan bahwa pengaturan hukum terhadap industri halal di Nigeria berpotensi menciptakan peluang yang lebih luas dalam sektor perdagangan dan komersial, antara lain melalui peningkatan produksi pangan lokal, pembentukan keterkaitan ekonomi, pengembangan pasar ekspor, pertumbuhan sektor pariwisata dan perhotelan, serta penciptaan lapangan kerja yang signifikan. Namun demikian, sejumlah tantangan seperti keterbatasan infrastruktur, akses pembiayaan yang belum memadai, serta belum optimalnya kerangka regulasi dapat menghambat pertumbuhan industri ini. Oleh karena itu, tantangan-tantangan tersebut perlu segera diatasi. Tulisan ini menyimpulkan bahwa melalui intervensi kebijakan yang tepat serta dukungan investasi yang memadai, industri ?al?l di Nigeria memiliki potensi untuk menghasilkan manfaat ekonomi, sosial, dan lingkungan yang signifikan.]